ANALYSIS OF ENTREPRENEURIAL MOTIVATION IN COLLEGE STUDENTS - PutieMaharani Basa; Nurullah Sururi Afif (CV. Radja Publika, 2025)
Entrepreneurship plays an important role in economic growth and reducing unemployment, especially in developing countries like Indonesia. Although the government and universities have encouraged students to become entrepreneurs, many of them still choose careers as office workers. This study aims to identify the motivational factors that drive Indonesian students to become entrepreneurs, using motivational theories developed by Indonesian scientists. This study focuses on key factors such as family influence, financial opportunities, and socio-cultural norms that are believed to play an important role in entrepreneurial motivation. Data were obtained from 100 students through questionnaires, which were then analyzed using quantitative methods to see the relationship between these factors and entrepreneurial interest. The results of the study indicate that family support and financial motivation have a significant influence in encouraging students' entrepreneurial interest. These findings are expected to help universities in designing entrepreneurship programs that are more effective and relevant to local values.